Machining the Surface of Orthopedic Stent Wire Using a Non-Toxic Abrasive Compound in a Magnetic Abrasive Finishing Process - Jeong Su Kim; Lida Heng; Sieb Chanchamnan; Sang Don Mun (Applied Sciences, 2021)
The orthopedic stent wire is one of the critical medical components, which is mainly used for the replacement of physically damaged parts in the human body. Therefore, a smooth surface and lack of toxic substances on the surface of this component are highly demanded. In this study, a magnetic abrasive finishing (MAF) process was carried out using a non-toxic abrasive compound (a mixture of iron powder, diamond particles, cold cream, and eco-friendly oils) to achieve high-quality surface finishing of orthopedic stent wire. The surface roughness (Ra) of the stent wire was investigated according to various processing parameters: different rotational speeds (500, 1000, and 2000 rpm), diamond particle sizes (1.0 µm), and three eco-friendly oils (olive oil: C98H184O10; grapeseed oil: C18H32O2; and castor oil: C57H104O9) within 300 s of the finishing time. The results showed that the surface roughness of the wire was reduced to 0.04 µm with a rotation speed of 1000 rpm and a diamond particle size of 1 µm when using grapeseed oil. SEM microimages and EDS analysis showed that the MAF process using a non-toxic abrasive compound could improve the surface quality of orthopedic Ni-Ti stent wire with a lack of toxic substances on the surface finish.